Dissolution of Marriage on the Grounds of Cruelty: A Comparative Overview of Fasakh and Irretrievable Breakdown of Marriage Principles - Md Hashim, Noraini; Abas, Afridah; Abd Hak, Nora (Journal of Malaysian and Comparative Law, 2019)
In Islam, if a husband treats his wife with cruelty, either physically or mentally, she has the right to apply to the court for the marriage to be dissolved, on the grounds of fasakh. In Malaysia, the practice is that the Syariah Court will ask the wife to provide sufficient evidence to prove her claim, failure of which the application for fasakh will be set aside. In some cases, a Syariah Court demanded on a higher standard or proving the act of cruelty by the husband. For example, a Syariah Court had insisted on the requirement of two male witnesses, who saw the act of beating the wife. This has caused difficulty to the wife as it would not be easy for her to fulfil this requirement. Whilst, section 54(1)(b) of the Law Reform (Marriage & Divorce) Act, 1976, states that the plaintiff may petition for divorce on the grounds that the respondent has behaved in such a way and thus, the plaintiff cannot be reasonably be expected to live with the respondent. The act of cruelty of the respondent, either physically or mentally is more than adequate to the term “behaviour” as stated under the present divorce law. In the case of irretrievable breakdown of marriage, both objective and subjective tests have been used by the court to decide whether or not the plaintiff can reasonably be expected to live with the respondent in consequence of the respondent’s behaviour including cruelty. If it is proven, then the application for divorce will be granted by the court. The article examines the above issues relating the methods of proof and evidentiary requirement in cruelty cases. Relevant legal provisions as provided under the Malaysian laws i.e., the LRA 1976 and the Islamic Family Law / Enactments and the practice of the Malaysian courts deliberating this issue are the focus of the article. Decisions of the Syariah and Civil Courts on cruelty in divorce cases are analysed to highlight the practice in Malaysia.